Amphiphilic metabolites in gallbladder bile: Potential biomarkers for gallbladder diseases. Issue 7 (8th August 2016) - Ko, Hyeji; Choi, Ikjang; Chang, Kyeol; Jeong, Gijin; Gong, Gyeonghyeon; Seo, Hyeonglim; Ryu, Donghyun; Lee, Kyeong Geun; Choi, Dongho; Chung, Hoeil; Lee, Youngbok
ABSTRACT: Gallbladder bile is one of the most abundant body fluids, and metabolic compositions of the bile are highly correlated with several gallbladder diseases (gallstones, gallbladder polyps, cholecystitis, and biliary tract cancer). The gallbladder diseases are generally diagnosed by several different imaging methods in the clinic; however, none of them can readily reveal detailed information about the diseases in molecular levels. Here, we have applied various nuclear magnetic resonance spectroscopy in order to identify and analyze composition of the human gallbladder bile, since the spectroscopic method provides not only structural information but also dynamic information of low- and high-weighted metabolites. In combination with both 1D Carr–Purcell–Meibom–Gill filtered 1 H spectrum and 2D 1 H– 13 C heteronuclear single quantum correlation spectrum, 15 metabolic compounds have been assigned in the bile specimen. Discrimination and classification analysis have been conducted by principal component analysis and support vector machine, respectively, so as to differentiate the gallbladder diseases, especially between gallstones and gallbladder polyps in here. From these investigations, we found two family of metabolites, namely bile acids (glycine and taurine conjugated cholic acids) and phosphatidylcholine, which play significant roles in discriminating gallstones, gallbladder polyps, and others.